1999
DOI: 10.1093/jn/129.12.2135
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated Linoleic Acid–Enriched Butter Fat Alters Mammary Gland Morphogenesis and Reduces Cancer Risk in Rats

Abstract: Conjugated linoleic acid (CLA) is a potent cancer preventive agent in animal models. To date, all of the in vivo work with CLA has been done with a commercial free fatty acid preparation containing a mixture of c9,t11-, t10,c12- and c11,t13-isomers, although CLA in food is predominantly (80-90%) the c9,t11-isomer present in triacylglycerols. The objective of this study was to determine whether a high CLA butter fat has biological activities similar to those of the mixture of free fatty acid CLA isomers. The fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
234
1
18

Year Published

2000
2000
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 391 publications
(258 citation statements)
references
References 23 publications
5
234
1
18
Order By: Relevance
“…Abbreviations: ADF, acid detergent fibre; CLA, conjugated linoleic acid; CP, crude protein; DM, dry matter; EE, ether extract; FAMEs, fatty acid methyl esters; NDF, neutral detergent fibre; OM, organic matter; SO, sunfloweroil; HPO, hydrogenated palm oil; LCFA, long-chain fatty acids; PUFA, polyunsaturated fatty acids; TMR, total mixed ration; VA, vaccenic acid.most abundant CLA, is considered to have anticarcinogenic properties (Ip et al, 1999), while frans-10, cis-12 CLA is capable of lowering body fat and increasing lean body mass (Park et al, 1999). trans-10, cis-12 CLA also decreases the concentration of fat in cow milk (Peterson et al, 2002) and of ewe milk (Lock et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviations: ADF, acid detergent fibre; CLA, conjugated linoleic acid; CP, crude protein; DM, dry matter; EE, ether extract; FAMEs, fatty acid methyl esters; NDF, neutral detergent fibre; OM, organic matter; SO, sunfloweroil; HPO, hydrogenated palm oil; LCFA, long-chain fatty acids; PUFA, polyunsaturated fatty acids; TMR, total mixed ration; VA, vaccenic acid.most abundant CLA, is considered to have anticarcinogenic properties (Ip et al, 1999), while frans-10, cis-12 CLA is capable of lowering body fat and increasing lean body mass (Park et al, 1999). trans-10, cis-12 CLA also decreases the concentration of fat in cow milk (Peterson et al, 2002) and of ewe milk (Lock et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous health benefits have been attributed to single CLA isomers in experimental animal models, including actions to reduce carcinogenesis, atherosclerosis, onset of diabetes, and body fat mass (Belury, 2002, Ip et al, 1999, Lee et al, 1994and Parodi, 1997. Major dietary sources of CLA are foods from ruminants, especially dairy products, where cis-9, trans-11 18:2, also named rumenic acid (RA) is the predominant CLA isomer.…”
Section: Introductionmentioning
confidence: 99%
“…The c9t11 CLA isomer has been shown to be anti-carcinogenic (Ip et al, 1999), while the t10c12 CLA isomer has been shown capable of decreasing body fat and increasing lean body mass (Park et al, 1999). The t10c12 CLA isomer also decreases fat concentration in dairy cows' milk in a dose-dependent fashion (Peterson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%